2016
DOI: 10.1080/10413200.2016.1194909
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Evidence-Based Parent Education in Organized Youth Sport: A Pilot Study

Abstract: Although existing literature in organized youth sport illuminates developmentally appropriate parent involvement behaviors, practitioners have yet to effectively disseminate evidence-based tools and strategies to parents. The purpose of the present pilot study was to design, implement, and assess an evidence-based education program for parents in organized youth sport. 39 fathers and 42 mothers from seven youth soccer teams were assigned to full-, partial-, or nonimplementation conditions. Parents and their sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 33 publications
2
83
0
1
Order By: Relevance
“…Expanding beyond the presentation model used by Dorsch and colleagues [49], both and Christensen [51]. Together, these two articles provide clear support for the value of utilizing reflective, practical activities to facilitate parents" understanding and awareness of their involvement.…”
Section: Strategies To Enhance Parental Involvement In Sportmentioning
confidence: 84%
See 1 more Smart Citation
“…Expanding beyond the presentation model used by Dorsch and colleagues [49], both and Christensen [51]. Together, these two articles provide clear support for the value of utilizing reflective, practical activities to facilitate parents" understanding and awareness of their involvement.…”
Section: Strategies To Enhance Parental Involvement In Sportmentioning
confidence: 84%
“…In one of the first evaluated parent-education interventions, Dorsch and colleagues [49] conducted a pilot study with 81 parents from seven U8 or U10 soccer teams. Parents were separated across three groups: a full intervention group, who received a researchinformed 45 minute presentation along with an education guide; a partial intervention group who received only the guide, and; a non-implementation group who received no information.…”
Section: Strategies To Enhance Parental Involvement In Sportmentioning
confidence: 99%
“…Parents have a natural role in providing support to their child before, during and after sport participation (Tamminen and Holt 2012). Indeed, a recent pilot study of parental education found that sport was a particularly useful environment to target parent behaviours and parent-adolescent relationships (Dorsch et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Athletes' psychological variables conducive to achievement in sport. While the parental involvement literature has often focused on children's achievement goals as an outcome of primary interest, a body of research suggests that parental involvement may have its most direct influence on children's attributes that lead to achievement (e.g., Allen, 2003;Babkes & Weiss, 1999;Chan, Lonsdale, & Fung, 2012;Dorsch, King, Dunn, Osai, & Tulane, 2016;Woolger & Power, 2000). Thus, the model of parental involvement in sport (Teques & Serpa, 2009 identifies four psychological variables associated with athletes' achievement which are susceptible to the influence of parents' behaviours: self-efficacy, intrinsic motivation, self-regulation, and social self-efficacy in relating to coaches.…”
Section: [Insert Figure 1]mentioning
confidence: 99%